Tingkat Kerusakan dan Kerugian Serangan Spodoptera frugiperda pada Jagung - Novi Ariska; Nurul Triagtin; Ranti Nur Fadillah; Rizki Putri Amelia; Shera Margaretha; Winda Pratiwi; Harman Hamidson (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Ariska N, Triagtin N, Fadillah RN, Amelia RP, Margaretha S, Pratiwi W, Hamidson H. 2021. Damage and loss of spodoptera frugiperda attack on corn plants. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 348-354. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Spodoptera frugiperda attack on corn is one of the important problems in corn cultivation which causes damage to corn plants. The purpose of this study was to determined the level of damage and loss to corn crops on agricultural land by S. frugiperda and to determined the appropriate control method to suppress the damage caused by S. frugiperda. The methodology used in this research was an approach through literature study. Based on several literature studies to suppress the population of S. frugiperda, can be used biological control by using natural enemies of S. frugiperda. Synthetic insecticide controlled was also used, but not safed for the environment. To knowing the appropriate corn plants to avoid pest attacks. The level of damage due to S. frugiperda in 2019 in African and European countries reached 8.3-20.6 tons a year with lost between US 2.5-6.2 million a year. The damage caused by S. frugiperda to corn was about 60%.